2021
DOI: 10.31234/osf.io/j6upw
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effects of item distinctiveness on the retrieval of objects and object-location bindings from visual working memory

Abstract: Visual working memory (VWM) is prone to interference from stored items competing for its limited capacity. These competitive interactions can arise from different sources. For example, one such source is poor item distinctiveness causing a failure to discriminate between items sharing common features. Another source of interference is imperfect binding, a problem of determining which of the remembered features belonged to which object or which item was in which location. In two experiments, we studied how the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 68 publications
(85 reference statements)
1
1
0
Order By: Relevance
“…The results showed that there were no effects of object distinctiveness on correct memory rate or P guess . The operational definition for conceptual distinctiveness of objects adopted here differs from Markov and Utochkin (2021) , yet our findings were consistent with theirs.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The results showed that there were no effects of object distinctiveness on correct memory rate or P guess . The operational definition for conceptual distinctiveness of objects adopted here differs from Markov and Utochkin (2021) , yet our findings were consistent with theirs.…”
Section: Discussionsupporting
confidence: 89%
“…Although we prolonged the encoding time in the sample display phase, the null-effect of conceptual distinctiveness on VWM was still confirmed. Similarly, Markov and Utochkin (2021) used low- and high-conceptual distinctiveness real-world object samples from Konkle et al (2010) to require participants to finish a working memory recognition task. The results showed that there were no effects of object distinctiveness on correct memory rate or P guess .…”
Section: Discussionmentioning
confidence: 99%